Evaluation of the quality of water used in Maysan Oil Factory (Vegetable Oil Factories\Ali Al-Hadi Factories) - pcadmin, Assistant Lect. Saad Farhan Banyan (Global Scientific Publishing, 2025)
The now adays study was conducted to evaluate the quality of water used in the vegetable oil factory in Maysan (Vegetable Oil Factories/Ali Al-Hadi Factories) and its potential impacts on the physical and chemical properties of the Amara River. The study was conducted from April to July 2024. Three sites were choosed in addition to a reference sample of river water. The measured values of temperature, acidity, electrical conductivity, turbidity, total dissolved solids, total basicity, nitrate, phosphate, sulfate, and positive ions of calcium, magnesium, sodium, and potassium ranged from 324 (689-116 mg/L) NTU(65-20)(28-29) (7.9-8.9) (1243-1420) dsm( 487) mg/L (14-78) mg/L (34-56) mg/L (456-654) mg/L (45-187) mg/L (54-35) mg/L (76- 123) mg/L (45-78) mg/L, respectively. The results showed significant differences between the studied properties with a significant increase in some studied properties compared to the permissible limit for wastewater. At the end of the study, it was recommended that these waters be monitored continuously and that a rapid review and comprehensive assessment of these pollutants be conducted in these locations in the future.
Keywords: Pollution; Water; Ali Al Hadi Factories